Influence of pre-incubation storage period on fertility, hatchability and embryonic - CHURCHIL, R R; NARAYANANKUTTY, K; PRAVEENA, P EZHIL; JOSEPH, PREETHYMOL (The Indian Journal of Animal Sciences, 2011)
A study was conducted to assess the effect of length of pre-incubation storage on fertility, hatchability and mortality pattern of embryos in 2 White Leghorn breeding flocks aged from 67 to 80 weeks. Eggs from IWN strain (8478 eggs) and from IWP strain (8801 eggs) were utilized in 5 hatches in this experiment. All the traits except hatchability on total egg set and DIS differed with the strain. Fertility was significantly higher in IWN strain; while hatchability (on fertile eggs set) was significantly better in IWP strain. Compared to IWP, IWN strain showed significantly higher early embryonic death (EED), total embryonic mortality (TEM), weaklings (WL) and rotten eggs (RE); however, incidence of dead germs (DG) was significantly higher in IWP than IWN strain. Hatchability of total and fertile eggs had significant negative correlation with egg storage period in both the strains. DG and TEM had significant positive correlation with storage length in both the populations; while, EED had significant positive correlation with storage length in IWN strain alone. EED, DG and TEM had significant negative correlations with hatchability on both total and fertile eggs in both the strains. TEM had significant positive correlation with EED and DG in both the strains. Regression analysis revealed significant reduction of hatchability of total and fertile eggs over storage period (d) in both the strains. On the other hand DG and TEM significantly increased with increasing storage length in both the flocks.